2019
DOI: 10.1002/mnfr.201801339
|View full text |Cite
|
Sign up to set email alerts
|

Wolfberry‐Derived Zeaxanthin Dipalmitate Attenuates Ethanol‐Induced Hepatic Damage

Abstract: Scope: Besides abstinence and nutritional support, there is no proven clinical treatment for patients with alcoholic fatty liver disease (AFLD). Here, the therapeutic effects and mechanisms of action of wolfberry-derived zeaxanthin dipalmitate (ZD) on AFLD models are demonstrated. Methods and results: The hepatoprotective effects of ZD are evaluated in vitro and in vivo. Direct interacting receptors of ZD on cell membranes are identified by liver-specific knockdown and biophysical measurements. Downstream sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Similar protective effects were reported by Gao et al [90]. In this study, seven-week-old male Sprague-Dawley rats were fed a liquid diet, and one group had alcohol added progressively.…”
Section: Effects Of Zeaxanthin In Human Healthsupporting
confidence: 82%
“…Similar protective effects were reported by Gao et al [90]. In this study, seven-week-old male Sprague-Dawley rats were fed a liquid diet, and one group had alcohol added progressively.…”
Section: Effects Of Zeaxanthin In Human Healthsupporting
confidence: 82%
“…The genetic depletion of Parkin accelerates acute and chronic and also, acute alcohol binge-induced liver injury and steatosis, which is likely due to impaired mitophagy in hepatocytes [114]. Compounds that are able to restore mitophagy inhibited by alcohol are able to attenuate liver injury in chronic alcohol feeding models [115,116]. These results indicate the protective role of mitophagy in alcoholic liver injury, and how targeting mitophagy may be a prospective therapeutic approach of ALD [117,118].…”
Section: Mitophagy In Aldmentioning
confidence: 92%
“…Decompensated mitophagy causes the release of mitochondrial damage-associated molecular patterns (mtDAMPs) that promote inflammatory and profibrogenic response, which in turn impair hepatic mitophagy, contributing to the pathological progression of ALD [121]. Impaired mitophagy was reported in the majority of chronic alcohol feeding cases [115,116,122], underscoring its potential critical role in the pathogenesis of ALD. Interestingly, mitochondrial fission protein Drp1 was activated in primary mouse hepatocytes treated with ethanol for 48 h, leading to mitochondrial fragmentation, which is associated with depressed FUNDC1-mediated mitophagy [122].…”
Section: Mitophagy In Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as ethanol induces hepatocyte apoptosis, ZD downregulated the mRNA expressions of proapoptosis genes Bax-1 and caspase-3/7 and upregulated the expression of Bcl-2 [59]. Another study [99] established the ability of ZD to ameliorate liver histology in the ALFD model and decrease serum levels of ALT and AST. The authors showed ZD binding to two receptors, P2X7 and adipoR1, which in turn induced mitophagy.…”
Section: Zeaxanthin Dipalmitate and Liver Diseasementioning
confidence: 99%